Performance Analysis 2000cc Gasoline Engine by Using Hydrogen – Pertamax Fuel Mixture - Caturwati, Ni Ketut; Sudrajad, Agung; Raditya, Putu Evan (Universitas Sultan Ageng Tirtayasa, 2025)
The use of motor vehicles has led to an increased demand for fossil energy sources as the main fuel and produce air pollution. Therefore, there is a need for alternative energy which is hydrogen. This research, we analyzes the performance of a 2000cc gasoline engine with hydrogen as a mixture with Pertamax fuel, varying the engine speeds at 2000, 2500, 3000, and 3500 rpm. The variable of hydrogen flow rates at 0.6, 1.2, and 1.8 lpm. The experimental results obtained that the addition of hydrogen as a dual fuel have an impact on the increase in the alternator power output in 15% at the difference 0 lpm and 1.8 lpm of hydrogen flow rates. The thermal efficiency also increases with the addition of hydrogen reach to 10.46%. The specific fuel consumption shows decrease at 2000 rpm on 34% between 0 lpm and 1.8 lpm. The emissions of HC and CO were decrease, while CO2 increases with the addition of hydrogen.